Anatomical Exploration of Sthapani Marma: A Review - Priyanka Devatwal; Sonia Meend (International Journal of Ayurveda and Pharma Research, 2021)
Marma are the vital points present in the human body explained in different Ayurveda classical texts. These are not only present as surface landmarks in the body but these are deeply seated physio-anatomical structures. Marma is defined as confluence of Mamsa, Sira, Snayu, Asthi and Sandhi at a particular point and it is the seat of Prana. According to Ayurveda, there are 107 Marma in the body. They are classified into various groups depending on the region, structure, prognosis, number and measurement etc., mainly by Acharya Sushurta and Vagbhatta. In Aghata (injury) of Vishlyaghna Marma, the person survives till the foreign body/weapon is at the wound place and will die as soon as the weapon is removed. A person can survive only if the foreign body has dropped by itself after Paaka (suppuration). Vishalyaghna Marma is Vayu dominant Marma points. Sthapani is one of the Vishalyghna Marma. It is present between the two eyebrows or the superciliary arches. The word Varmam and Marmam holds the same meaning in Tamil language. Varmalogy is a therapeutic manipulation of Varmam points where the Pranic energy gets concentrated or blocked. When a particular Varmam point gets stimulated, this energy is released from there and brings relief to the affected area of a person by regulating the flow of this energy which is obstructed due to assault on specific points. According to Siddha science, Tilartha Kalam is present on the same location as of the Sthapani Marma (as per the Ayurveda science) i.e. Glabella region. Through this article, we will try to explore the structures undercover the Sthapani Marma and also try to correlate the Sthapani Marma according to Siddha science along with the methods to stimulate the particular Varmam point.